Social Mission of Students in the Educational Process : The Past and the Prezent - Maksymovska, N. (My University, 2019)
The article considers the interconnection between students’ social mission in the conditions of information society and improvement of higher educational process. The aim and tasks of the article are to examine the dynamics of students’ social mission, to study out the characteristic features of improving educational process in relation to contemporary tasks of training a competent professional, empiric verification of proposed scientific positions. To investigate the connection between students’ social mission and optimization of educational process a set of methods was used: theoretical – historical analysis to define students’ social mission; comparison, generalization of scientific facts to uncover contemporary interaction tendencies of students’ social role and the flow of educational process; synthesis for clarification of the “students’ social mission” concept; empiric – experimental research of students’ satisfaction with the educational process, survey through online questionnaire, mathematic processing and generalization of acquired data. Analysis of open-type responses regarding the proposed remarks and recommendations enabled the formation of action directions to improve the conditions of educational process, such as support and facilitation of students’ academic mobility, usage of new forms and means in educational process (distance learning, training, contemporary information technologies and others), correspondence of the contents of educative qualification study programs with contemporary demands of a job market and others. Results of this study will be useful for scholars of social pedagogy, teachers, methodologists and heads of higher educational institutions, social pedagogues, social workers, students, etc.
Keywords: здобувачі вищої освіти; освітньо-виховний процес; заклади вищої освіти; social mission; інформаційне суспільство; educational process; information society; higher education institution; students